To find the value of k, we need to determine the derivative of the given function y=(2x−1)ekx at x=1
step 2
The derivative of y with respect to x is y′=dxd[(2x−1)ekx]. Using the product rule, y′=(2)ekx+(2x−1)kekx
step 3
Evaluate the derivative at x=1 to find the slope of the tangent line: y′(1)=(2)ek(1)+(2(1)−1)kek(1)=2ek+kek
step 4
The slope of the tangent line at x=1 must be equal to the slope of the line y=5ex at x=1, which is 5e
step 5
Set the expression for y′(1) equal to 5e and solve for k: 2ek+kek=5e
step 6
Factor out ek from the left side of the equation: ek(2+k)=5e
step 7
Divide both sides by e to isolate ek−1(2+k): ek−1(2+k)=5
step 8
Since ek−1=ek/e, we have (ek/e)(2+k)=5
step 9
Multiply both sides by e to get ek(2+k)=5e
step 10
We already have ek(2+k)=5e from step 6, so we can see that k must be such that 2+k=5
step 11
Solve for k: k=5−2
step 12
Simplify to find k: k=3
Answer
k=3
Key Concept
Finding the slope of a tangent line to a curve at a given point
Explanation
The slope of the tangent line to the curve y=(2x−1)ekx at x=1 is found by differentiating the function and evaluating it at x=1. This slope must match the slope of the line y=5ex at x=1, which leads to the equation ek(2+k)=5e. Solving this equation for k gives the value of k as 3.
Not the question you are looking for? Ask here!
Enter question by text
Enter question by image
Unlock Smarter Learning with AskSia Super!
Join Super, our all-in-one AI solution that can greatly improve your learning efficiency.